Metal Matrix Composites - Chawla, Nikhilesh. (Springer New York : Imprint: Springer, 2013)
Metal Matrix Composites (MMCs) have progressed from “niche” materials to high performance applications in aerospace, electronic packaging, automotive, and recreational products. This book focuses on the synergistic relationships among processing, microstructure, and properties of metal matrix composites. The authors include chapters on reinforcements, common matrix materials, processing of MMCs, interface characterization and techniques for obtaining interfacial properties, monotonic mechanical and physical properties, cyclic fatigue, creep, wear resistance, corrosion, and applications of MMCs. This, 2nd edition, builds on the text of the previous edition, by adding new and contemporary coverage of nanocomposites, corrosion, new applications, and new characterization techniques such as x-ray tomography and micropillar compression.